HPLC Estimation of Perindopril Erbumine in Tablet Dosage Form - Singh, Mahaveer; Kaskhedikar, S.G.; Singhvi, Gautam; Soni, Love (Asian Journal of Chemistry, 2011)
In the present investigation, a simple method for estimation of coversyl has been developed with a simple mobile phase (Hypersil, C8, 250 × 4.6 mm, 5 μm column). Mobile phase was made up of heptane sulphonic acid buffer (pH 2.0) and acetonitrile in ratio of 60:40. Detector used was a UV detector and detection was carried out at 215 nm. Linearity was determined at five levels over the range of 60 to 140 % of working concentration.